Percutaneous image-guided ablation of bone metastases: local tumor control in oligometastatic patients. (1st January 2019) - Luigi Cazzato, Roberto; Auloge, Pierre; De Marini, Pierre; Rousseau, Chloé; Chiang, Jeanie Betsy; Koch, Guillaume; Caudrelier, Jean; Rao, Pramod; Garnon, Julien; Gangi, Afshin
Abstract: Introduction: Percutaneous image-guided cryo- (CA) and radiofrequency- (RFA) ablations have been widely used in the treatment of painful bone metastases (BM). However, paucity of data is available for the performance of these treatments when used with a curative intent. The aim of this study is to investigate the local progression free-survival (LPFS) after radical percutaneous image-guided ablation of BM in oligometastatic patients, and to identify predictive factors associated with local tumor progression. Materials and Methods: This is a retrospective review of all patients who underwent percutaneous image-guided CA or RFA of BM with a radical intent between 2007 and 2018. Results: Forty-six patients with a total of forty-nine BM underwent percutaneous image-guided CA ( N  = 37; 75, 5%) or RFA ( N  = 12; 24, 5%). Primary malignancies included thyroid ( N  = 11, 22.5%), breast ( N  = 21; 42.9%), lung ( N  = 8; 16.3%) and other ( N  = 9; 18, 3%) cancers. Additional consolidation was performed after ablation in 20.4% cases ( N  = 10). Mean follow-up was 34.1 ± 22 months. Local progression at the treated site was observed in 28.5% cases ( N  = 14); 1- and 2-year LPFS was 76.8% and 71.7%, respectively. Size of BM (>2 cm) predicted local tumor progression ( p  = .002). Conclusions: Percutaneous image-guided locoregional therapies used in the radical treatment of BM in oligometastatic patients demonstrate significant rates of LPFS providing the size of BM ≤2 cm.